Designing An Accounting Information System Based On Microsoft Access At Tua’i Yang Laundry - Androni Susanto; Dhea Ananda Syahputri (Universitas Internasional Batam, 2023)
Tua'I Yang Laundry is an UMKM established by Mr. Jammer Pasaribu in 2016, located at Perum Bambu Kuning, Batu Aji. Tua'I Yang Laundry is a service of washing clothes, and provide for washing dolls, carpets, bags, clothes, and shoes. The price in this laundry has been set by the service provider with a certain time limit. Accounting system Tua'I Yang Laundry is still using manual system, the owner Mr. Jammer Pasaribu is the one who does the recording process and still lack of knowledge in making computerized transactions. Therefore, this community service activity aims is to design an accounting recording system with Microsoft Access so that it is expected to make it easier to record income and expenses while at the same time assisting in developing certain Tua'I Laundry according to the applicable Accounting Standards (SAK). The method used is interview, observation, and documentation. The resulting information system is a Microsoft Access system which consists of an information form, namely a customer form, laundry service prices and others, then a transaction form, namely a laundry service sales form. In addition, reports are in the form of income statements, changes in capital, financial position. The implementation of the system was carried out well and could assist in compiling reports more easily and improve the quality of bookkeeping at Tua'I Yang Laundry.